Enthalpy efficiency of the soleus muscle contributes to improvements in running economy - Bohm, Sebastian (Proc Biol Sci, 2021)
During human running, the soleus, as the main plantar flexor muscle, generates the majority of the mechanical work through active shortening. The fraction of chemical energy that is converted into muscular work (enthalpy efficiency) depends on the muscle shortening velocity. Here, we investigated the soleus muscle fascicle behaviour during running with respect to the enthalpy efficiency as a mechanism that could contribute to improvements in running economy after exercise-induced increases of plantar flexor strength and Achilles tendon (AT) stiffness. Using a controlled longitudinal study design (n = 23) featuring a specific 14-week muscle–tendon training, increases in muscle strength (10%) and tendon stiffness (31%) and reduced metabolic cost of running (4%) were found only in the intervention group (n = 13, p < 0.05). Following training, the soleus fascicles operated at higher enthalpy efficiency during the phase of muscle–tendon unit (MTU) lengthening (15%) and in average over stance (7%, p < 0.05). Thus, improvements in energetic cost following increases in plantar flexor strength and AT stiffness seem attributed to increased enthalpy efficiency of the operating soleus muscle. The results further imply that the soleus energy production in the first part of stance, when the MTU is lengthening, may be crucial for the overall metabolic energy cost of running.